Pengaruh Penambahan Minyak Ikan Sulfonasi Pada Proses Penyamakan Terhadap Karakteristik Kulit Kambing Tersamak Untuk Atasan Sepatu - Mutiar, Sri; Anggia, Malse; Angre, Angre (LPPM Universitas Dharma Andalas, 2025)
Fatliquoring is an important component in tanned leather that serves to make the leather soft during the Fatliquoring process. Tanned leather with oiling will produce tanned leather that is limp, softer and produces high pliability, defending the leather from damage by the influence of water. In addition, the Fatliquoring process absorbs and repels water molecules. The tanning process generally starts from rawhide, hair removal, weak removal, neutralization, pickle mineral tanning, vegetable tanning, re-tanning, and finishing. The purpose of this research is to apply fish oil so that it can change the properties of tanned leather to become softer, more flexible, more clayey, more flexible and the elephant surface becomes smoother. The research method is various treatments of sulfone Fatliquoring fish oil concentration on tanned goat skin. The materials used in this experiment were salt-tanned goat skins. Analysis of the quality of tanned leather is determined from the characteristics of tanned leather measuring the physical and organoleptic properties of tanned leather. The resulting tanned goatskin meets the SNI Standard of leather.